PENDIDIKAN KECAKAPAN HIDUP (LIFE SKILL) DALAM PEMBELAJARAN SAINS DI SD/MI - SHAWMI, AYU NUR (Universitas Islam Negeri Raden Intan Lampung, 2015)
Education is one of the manifestations of human culture that is dynamic and developmental requirements. Therefore, changes or educational development is that it should happen in line with the changing culture of life. Changes in the sense of improving education at all levels should continue to be done in anticipation of future interest. Education which has been implemented in Indonesia is already very good quality, but there are some things you forgotten so felt less effective teaching method. One of the most important yet often overlooked is life skills or life skills. This is emphasized in the effort to develop generic skills namely personal skills and social skills. This does not mean that specific skills are skills for academic and vocational skills are not developed, although it was only in the early stages of development or introduction